In Vitro Cultivation of 3D Umbilical Cord MSC Spheroid Model for Chondrogenic Differentiation - Bayu Tirta Dirja; I Gusti Ayu Sri Andayani; Yulfa Rizky Amita; Ahmad Taufik S; Dewi Suryani; Mohammad Rizki (Faculty of Medicine, Universitas Mataram, 2026)
Cartilage is a tissue that specifically difficult to heal when injured due to its avascular, aneural, and alymphatic nature, in addition to the limited ability of cells to migrate in the tissue for repair. Human umbilical cord–derived mesenchymal stem cells (hUC-MSCs) possess promising chondrogenic potential, particularly when cultured in three-dimensional (3D) systems that better mimic the native tissue environment. It is important to note that the current study is limited to an in vitro setting, and no in vivo experiments were conducted. This work aimed to evaluate the ability of hUC-MSCs to undergo chondrogenic differentiation over time using a 3D spheroid culture system. hUC-MSCs were isolated from umbilical cords of two donors, expanded to passage 5, and seeded into ultra-low attachment well plates with chondrogenic differentiation medium. Spheroids were incubated for 14 and 21 days. Chondrogenesis was assessed by crystal violet staining, and collagen deposition was analyzed microscopically and quantified using ImageJ software. Statistical analysis was performed using one-way ANOVA with Tukey’s post-hoc test. hUC-MSCs successfully formed spheroids and demonstrated progressive chondrogenic differentiation over time, marked by increasing collagen deposition. Significant increases in cartilage-positive areas were observed on day 14 (p<0.01) and further on day 21 (p<0.05), indicating enhanced cartilage matrix formation in vitro. Three-dimensional spheroid culture of hUC-MSCs effectively promotes chondrogenic differentiation, with substantial collagen accumulation observed after 21 days. This in vitro model provides a valuable platform for studying the sequential mechanisms of cartilage formation and holds potential for future applications in cartilage tissue engineering.